2022
DOI: 10.31234/osf.io/x4d3f
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The computational relationship between reinforcement learning, social inference, and paranoia

Abstract: Theoretical accounts suggest heightened uncertainty about the state of the world underpin aberrant belief updates, which in turn increase the risk of developing a persecutory delusion. However, this raises the question as to how an agent’s uncertainty may relate to the precise phenomenology of paranoia, as opposed to other qualitatively different forms of belief. We tested whether the same population (n=750) responded similarly to non-social and social contingency changes in a probabilistic reversal learning t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 46 publications
1
6
0
Order By: Relevance
“…But our data continue to suggest that paranoia and conspiracy theorizing -even the social aspects thereofare related to low-level domain-general primary learning mechanisms (30) which may be dopaminergically and noradrenergically mediated (31,32). This domain general contribution to paranoia involves learning expectancies about the environment and the agents within it (33), a process that may be guided by using oneself as a source of prior beliefs (18). Our data represent an extension of those processes into real world social relationships.…”
Section: Discussionsupporting
confidence: 65%
“…But our data continue to suggest that paranoia and conspiracy theorizing -even the social aspects thereofare related to low-level domain-general primary learning mechanisms (30) which may be dopaminergically and noradrenergically mediated (31,32). This domain general contribution to paranoia involves learning expectancies about the environment and the agents within it (33), a process that may be guided by using oneself as a source of prior beliefs (18). Our data represent an extension of those processes into real world social relationships.…”
Section: Discussionsupporting
confidence: 65%
“…Belief-based models have performed well in attribution tasks, over and above associative models (3,4), but the initial characterization of others appears faster than most models suggest (5,6). We took inspiration from recent work on black-and-white thinking (7) to hypothesize that in interpersonal situations, people attempt to quickly classify others' attributes as 'beneficial or detrimental' to themselves.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, this mechanism may not be speciftied to social contexts, but instead may be related to a more general deficit in learning under uncertainty (Reed et al, 2020;Suthaharan et al, 2021). However, we do note that the social control task employed by Suthaharan et al (2021) was not as ecologically valid as other tasks that were used to study paranoia such as the dictator game (Raihani and Bell, 2017;Barnby et al, 2020Barnby et al, , 2022 or our task which was adapted from empirically-observed human-human interactions in a previous study using videos of human advisers intending to either help or deceive players (Diaconescu et al, 2014). Finally, it is also possible that there are both domain-general and domainspecific changes, but that these can only be studied at the neuronal level and converge on the same behavioural model parameters.…”
Section: Is the Perception Of Environmental Volatility Alteredmentioning
confidence: 83%